Dynamic Imaging of Ostwald Ripening by Environmental Scanning Transmission Electron Microscopy. Issue 22 (8th October 2015) - Martin, Thomas E.; Gai, Pratibha L.; Boyes, Edward D.
Abstract: The first dynamic atomic resolution environmental scanning transmission electron microscope (ESTEM) study of the nanoparticle sintering of a model Cu system is reported. ESTEM confers the advantage of a Z‐contrast dependence in industrially representative conditions to provide enhanced visibility of sub‐nanometer particles when compared with TEM. The importance of this is demonstrated by the significant enhancement in the Ostwald ripening rate of model Cu nanoparticles in the presence of 3 Pa hydrogen, an effect that is independent of the substrates studied. Temperatures of 400–550 °C are shown to switch the operating regime of the rate‐limiting mechanism. Cu catalysts are used for methanol synthesis and hydrocarbon‐conversion processes for fuel cells, and the importance of observing these catalysts in their working states is demonstrated. Unique ESTEM observations of Ostwald ripening are combined with kinetic models to improve the technical understanding of catalyst deactivation mechanisms. Abstract : Cu later : Deactivation by the migration of single atoms (Ostwald ripening) is a key technical limit for industrial catalysis. By using a newly developed environmental scanning transmission electron microscope, the mechanism can be tracked at a single‐particle level in situ. H2 is found to significantly enhance the Cu Ostwald ripening rate, and kinetic modelling is used to deconvolute the cause.